Sejarah Berdiri Central Komite Khilafah di Hindia Timur (Studi Analisis Surat Kabar 1924 – 1926) - Lutfhi Anwari (Tarikh : Journal of Islamic History and Civilization, 2026)
This Al-Islam Congress was a political reaction by Muslims in the Dutch East Indies to the abolition of the global Islamic political institution known as the Caliphate, as well as the ousting of Caliph Abdul Majid II by Mustafa Kemal Pasha—with British assistance—on March 3, 1924. The purpose of this study is to analyze the history of the establishment of the Central Committee of the Caliphate in the Dutch East Indies (A Newspaper Analysis Study, 1924–1926). Employing a qualitative approach and historical research methods (heuristics, criticism, interpretation, and historiography), as well as an interdisciplinary approach, this study addresses a gap in the literature by combining historical, political, and social perspectives. The findings reveal that in mid-1924, several figures from the Arab community in Batavia and Surabaya received an invitation to the Caliphate Congress in Cairo sent by the scholars of Al-Azhar. Tjokroaminoto responded by organizing a meeting held on Saturday and Sunday, October 4–5, 1924, at the Madrasah Tarbiyatul Aitam building in Genteng, Surabaya. The invitation to the meeting was disseminated to all scholars and community leaders through the newspapers of the Islamic movement. Disagreements marked the proceedings of the meeting, until Wondo Soedirjo eventually suspended the session briefly. Once the atmosphere had calmed, the participants agreed to first establish a committee as a platform for their struggle. The meeting, held at Madrasah Tarbiyatul Aitam in Surabaya, resulted in the formation of the first organization in the East Indies dedicated to reestablishing the Caliphate. Attendees representing various Islamic organizations and several regional associations agreed to name this merged organization the Centraal Comite Chilaafat Hindia Timoer. The newspaper Soeara Perdamaian published the khittah, or guiding principles, of this movement.